Community, Immunity, and Vulnerability: Paradoxes and Possibilities in Postpandemic Diaconal Practice - Stålsett, Sturla J. (Religions, 2023)
This article discusses an inherent paradox in contemporary conceptualisations of community as a challenge to diaconia. Logics of protection separate insiders from outsiders, producing a fundamental antagonism between those who belong to the community and those who threaten it. During pandemics, this logic is exacerbated. When contagion threatens all, even the community needs to be protected from itself. Immunitarian defences are required for the safety of all community members. However, measures implemented to ensure immunity can also harm people’s mental and somatic health. This paradox presents ethical and practical challenges for inclusive justice, including diaconia. Concerning this dilemma, the article draws on Roberto Esposito’s reframing of community and immunitarian defence. Esposito argues that immunitarian mechanisms must promote tolerance of otherness through openness to its presence within. I suggest that this openness can be seen as a fundamental ontological vulnerability shared by all living creatures. Learning from recent contributions within vulnerability studies and feminist and trauma theologies, I employ Tony Addy’s concept of conviviality as a model for diaconal community building, seeking to elucidate the relevance of Esposito’s thinking to postpandemic diaconal practice.